A framework for ubiquitous IP communications in vehicle to grid networks (2011)
The electrical grid is a critical infrastructure that is slowly moving towards a more reliable and efficient supply system: the Smart Grid. As part of this migration process, a new group of energy-aware and emission-free technologies are being developed. Electric vehicles are a promising technology that belongs to that group. By connecting the electric vehicles to the grid, an energy-efficient cycle is created, in which the vehicles not only draw power from the grid, but they also send electricity back into it. For a successful vehicle to grid (V2G) interaction, a reliable and ubiquitous V2G communications network should be deployed. While previous research has focused on V2G data transmission when the vehicle is connected to the grid, we focus on the advantages of enabling the exchange of data while on-the-go by means of a wirelessly connected smart metering infrastructure network. Furthermore, this paper proposes a complete framework for the support of IP communications in mobile V2G environments.